A multiple endpoint approach reveals potential in vitro anticancer properties of thymoquinone in human renal carcinoma cells. (February 2020) - Costa, J.G.; Keser, V.; Jackson, C.; Saraiva, N.; Guerreiro, Í.; Almeida, N.; Camões, S.P.; Manguinhas, R.; Castro, M.; Miranda, J.P.; Fernandes, A.S.; Oliveira, N.G.
Abstract: Thymoquinone (TQ) is a monoterpene isolated from the oil of Nigella sativa seeds. The aim of this work was to evaluate the cytotoxic effects induced by TQ and its impact on the migration and invasion potential of 786-O human renal cancer cells. These cells were exposed to TQ (1–100 μM) for 24 and 48 h and cell viability assessed using the Crystal Violet and MTS assays. TQ treatment clearly decreased cell viability in a concentration- and time-dependent manner. TQ exposure moderately increased intracellular ROS levels and co-incubation with reduced glutathione markedly increased cell viability. Moreover, the effect of TQ in the cell cycle distribution was evaluated using flow cytometry, and an increase in the sub-G1 population was observed, especially at 30 μM, along with an increase in the % of apoptotic cells. TQ did not show genotoxic effects at a non-cytotoxic concentration (1.0 μM). At this concentration level, TQ significantly decreased the collective migration of 786-O cells, whereas it had no effect in chemotactic migration. TQ also decreased the invasiveness potential of 786-O cells, as evaluated by the transwell invasion assay. Overall, these results suggest that TQ presents an anticancer potential in the context of renal cancer, warranting further investigation. Highlights: TQ induces concentration and time-dependent cytotoxicity in 786-O cells. TQ induces ROS and the co-treatment with reduced glutathione increases cell viability of TQ-exposed cells. TQ at high concentrations increases the sub-G1 population and % of apoptotic cells. TQ decreases collective migration but not chemotactic migration of 786-O cells. TQ decreases the invasive potential of 786-O cells.